First successfully separated set of thoraco-omphalopagus twins in Ilorin, Nigeria: A case report - Lukman Olajide Abdur-Rahman; T K Raji; Abdulwahab O Lawal; Abdulrasheed A Nasir; O A Adesiyun; Mohammed B Abdulkadir; Olayinka Sayomi; Iyehunwa Ayinmode; I O Oyinloye; B O Bolaji; K A Adegboye; M B Adegboye; et al. (Journal of Clinical Sciences, 2023)
The birth of babies sharing body part(s) and surviving independently is indeed a scientific marvel. Conjoined twinning is a rare phenomenon with various presentations, having an estimated incidence of 1 per 200,000 live births. The successes recorded by experts in developed countries in the separation of conjoined twins in recent times, especially among those with complex unions are indeed fascinating. The management of conjoined twins presents a great challenge to medical and surgical teams in tropical African countries such as ours where we are faced with challenges of limited resources and facilities, even amidst the presence of well-trained experts. The incidence of conjoined twins is difficult to report in our practice because of failures that accompanied previous cases that were managed and not reported. This is the first successful separation after two previous failed attempts at our center. We report a case of successful surgical separation of thoraco-omphalopagus conjoined twins who were undiagnosed prenatally and delivered by emergency cesarean section following prolonged labor by a primiparous woman. Babies were joined from the lower chest and the upper abdomen and they shared a single umbilicus and omphalocele sac. No internal viscus was shared apart from the torso wall. They were cared for from 12 h of live until 127 days of live when they were successfully separated by a team of medical and surgical experts. This is a report of a successful separation of conjoined twins at the University of Ilorin Teaching Hospital in North Central Nigeria. Careful interdisciplinary conduct of expert activities will ensure the survival of rare congenital malformations such as conjoined twinning even in underdeveloped climes.